Taxanes for Breast Cancer during Pregnancy: A Systematic Review - Zagouri, F.; Sergentanis, T.N.; Chrysikos, D.; Dimitrakakis, C.; Tsigginou, A.; Zografos, C.G.; Dimopoulos, M.-A.; Papadimitriou, C.A. (Clinical Breast Cancer, 2013)
Landmark studies have established taxanes in the treatment of patients with breast cancer; however, recommendations regarding their administration during pregnancy are controversial. The present systematic review aims to synthesize all available data that stem exclusively from breast cancer case series to evaluate the efficacy and safety of taxanes during pregnancy. Overall, 16 studies (50 pregnancies) were eligible for the systematic review according to prisma guidelines. The mean age of patients with breast cancer at pregnancy was 34.6 years. The gestational age (GA) at chemotherapy administration varied from 12 to 36 weeks. The mean GA at delivery was 35.9 weeks. The mean weight of babies at delivery was 2380 g. In 76.7% of cases, a completely healthy neonate was born; in the remaining cases, a neonate who was dystrophic and premature, one with mild hydrocephalus, one with signs of bacterial sepsis, one with hyperbilirubinemia, one with apnea of prematurity, respiratory distress syndrome and gastroesophageal reflux, one with meconium-stained fluid, and another neonate with neutropenia and pyloric stenosis were reported. Ninety percent of children were completely healthy, with a median follow-up of 16 months; in the remaining cases, one child with recurrent otitis media, one with immunoglobulin A deficiency and mild constipation, and another child with delayed speech were reported. In conclusion, available data suggest that taxanes may potentially play a promising role in the optimal therapeutic strategy of patients with breast cancer diagnosed during pregnancy. © 2013 Elsevier Inc.
Keywords: breast cancer; Docetaxel; Paclitaxel; Pregnancy; Taxanes